2005
DOI: 10.1002/smi.1068
|View full text |Cite
|
Sign up to set email alerts
|

Health and emigration: subjective evaluation of health status and physical symptoms in Russian-speaking migrants

Abstract: This is a longitudinal study exploring self‐reported health status and physical symptoms of Russian‐speaking migrants (n = 307) from the states formed after the break up of the Soviet Union. These health status reports were compared with Russians in Russia (n = 300) and non‐immigrant native German test subjects (n = 310). Focus was on the change in subjective evaluation of physical health and adaptation to a new medical health care system as part of the acculturation process following migration. Migrants have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 22 publications
3
31
0
4
Order By: Relevance
“…Despite these positive anticipations, the respondents experienced upcoming migration as a relatively stressful event. However, their average stress level decreased after migration, and there was no difference between T 1 and T 2 assessments of psychological well-being, even though a decrease in well-being is typical for the postmigration stage (e.g., Kirkcaldy et al, 2005;Lerner et al, 2005;Ritsner & Ponizovsky, 1999;Ward, 2001). These positive findings may be explained by the different role of affective dimension as compared to the other two acculturation dimensions: Decreased psychological stress may be seen as a reactive response to ethnic migrants' positive acculturation experiences in the behavioral dimension of acculturation after migration (cf., Jasinskaja-Lahti, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Despite these positive anticipations, the respondents experienced upcoming migration as a relatively stressful event. However, their average stress level decreased after migration, and there was no difference between T 1 and T 2 assessments of psychological well-being, even though a decrease in well-being is typical for the postmigration stage (e.g., Kirkcaldy et al, 2005;Lerner et al, 2005;Ritsner & Ponizovsky, 1999;Ward, 2001). These positive findings may be explained by the different role of affective dimension as compared to the other two acculturation dimensions: Decreased psychological stress may be seen as a reactive response to ethnic migrants' positive acculturation experiences in the behavioral dimension of acculturation after migration (cf., Jasinskaja-Lahti, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Soziale Unterstützung, insbesondere durch Fami lienmitglieder, Freunde und Bekannte, stellt eine wichtige Ressource bei der Bewältigung von Stress und für die psychische Anpassung und Gesundheit im Verlauf des Übergangs von einer Kultur in eine andere dar [18]. Der Zusammenhang zwischen sozialer Unterstützung und psychischem Wohlbefinden von Migranten ist vielfach belegt.…”
Section: Soziale Unterstützungunclassified
“…Because the ethnic German migrants are among the largest immigrant groups in Germany, it is critical to study the subjective theories of health and illness of these groups. In a recent study, Kirkcaldy et al (2005) explored the subjective evaluation of health status and physical symptoms among Russian-speaking migrants in Germany, and found that migrants had more health problems than both Russians and the native population. In addition to general stress triggered by the process of migration, migrants suffered more from headaches and symptoms of exhaustion, which were interpreted as physical correlates of psychological pressure.…”
mentioning
confidence: 99%